Pengaruh Sikap Konsumen dan Manfaat yang Dirasakan terhadap Niat Beli Sabun Cuci Piring Berlabel Halal di Kota Bukittinggi - Rahma Yulia; Wikasanti Dwi Rahayu; Jon Kenedi; Rahmi Rahmi (Pusat Riset dan Inovasi Nasional, 2025)
Studies on purchase intentions for halal products have focused more on the food and cosmetics sectors, while halal products in non-food sectors such as dishwashing soap have rarely been studied, even though the existence of these products is also important for Muslim consumers. This indicates a research gap that needs to be filled, especially considering the importance of hygiene in Islamic teachings and the increasing public awareness of the halalness of household products. Bukittinggi City was chosen as the study location because it is dominated by Muslim consumers who have a high concern for halal certification. The aim of this study is to assess the extent to which consumer attitudes and perceived usefulness can influence purchase intentions for halal-labeled dishwashing soap in Bukittinggi City. This study was conducted using a quantitative approach and a survey was conducted by distributing questionnaires to 124 respondents. The PLS (Partial Least Square) technique in the SEM (Structural Equation Modeling) approach was applied to analyze the data, with the help of SmartPLS.3.0 software. The findings in this study show that consumer attitudes and perceived usefulness significantly influence purchase intentions. The conclusion of this research is that the more positive consumers' attitudes and the greater usefulness they perceive from non-food halal products, the greater their purchase intention. The implication of this finding is the importance of businesses adopting Sharia values and providing halal education in their marketing strategies for household products.